(untitled) (SigMe, 2025)
The training of obstetrics graduates requires an effective integration of theoretical knowledge with clinical practice to ensure quality care and maternal-infant safety. In this context, clinical simulation emerges as an innovative pedagogical strategy that allows students to acquire and practice competences in a safe and controlled environment, fostering reflective learning and decision-making without risk to patients. The objective of this research was to describe and analyze the implementation of clinical simulation in the Bachelor’s Degree in Obstetrics at the Faculty of Medical Sciences of the Universidad Nacional del Litoral (FCM-UNL), with the purpose of assessing its potential as an educational resource within the training process. A descriptive, non-experimental, cross-sectional study with a qualitative-quantitative approach was conducted. Data collection included surveys and interviews with the Faculty and the students, as well as observation of clinical simulation practices carried out at the Simulation and Interprofessional Health Education Center of FCM-UNL. The results show that the students perceive clinical simulation as a realistic experience (56.6%), which enhances the development of technical skills (71.1 %), facilitates the adaptation of simulated cases to theoretical knowledge (80.1 %), and promotes, almost unanimously, the integration between theory and practice (99 %). They also highlighted its value in strengthening motivation (96 %) and confidence in learning. The Faculty emphasized the importance of adequate scenarios and the consolidation of simulation as a structured educational strategy within the curriculum. This study confirms that clinical simulation is a highly valuable pedagogical tool for the training of obstetrics graduates, as it promotes the acquisition of technical and non-technical competencies, critical reflection, and teamwork. However, it is noted that its curricular inclusion is still uneven and not yet recognized as an accreditation standard in undergraduate education, which highlights the need to strengthen its systematic integration. Thus, clinical simulation stands as an innovative and necessary strategy in obstetric education, with the potential to optimize educational quality and contribute to maternal-infant care safety. Generating evidence to support its curricular integration is essential to guide well-founded institutional decisions, especially in contexts of budgetary constraints.